Effect of the information in the process of production and UNA's distribution metal mecanica's company - Chong Chong, Mario (2012)
The research is focused on a business game known as the beer game which was applied to a metal mechanic company. The main difference of this research, with respect to other studies, is the choice of participants (company staff performing similar roles). The methodology applied different scenarios to obtain the data and the results: unknown information, wellknown demand, cooperation and communication. The experimental results in a production and distribution system of a furniture company shows experimentally the value of access to information and its effect on profitability and business efficiency with the delivery of products and services in the time and the right place, avoiding unnecessary costs and inadequate management of resources.